2016
DOI: 10.1039/c6mb00576d
|View full text |Cite
|
Sign up to set email alerts
|

miR-186 regulates chemo-sensitivity to paclitaxel via targeting MAPT in non-small cell lung cancer (NSCLC)

Abstract: miR-186 has been reported to be implicated in tumorigenesis and chemoresistance in a few cancer types. However, its role in regulating chemoresistance has not been investigated in non-small cell lung cancer (NSCLC). To examine the effects of miR-186 on chemosensitivity in NSCLC, an miR-186 mimic and inhibitor were transfected, followed by CellTiter-Glo® assay in NSCLC cell lines. Western blot and luciferase assay were performed to investigate the direct targeting of miR-186. A xenograft mouse model was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 27 publications
0
36
0
Order By: Relevance
“…The group transfected with miR-186 and control constructs exhibited the minimum number of cells passing through the chamber, which could be abolished upon transfection with PTTG1 constructs. * P<0.05. perform a pivotal role in muscle differentiation (14), miR-186 has also been found to participate in many biological and pathological processes, including cell proliferation, apoptosis and invasion (7,15). Recently, the tumor suppressive role of miR-186 has been widely reported in many cancers, such as in prostate cancer (PC), where miR-186 inhibited the expression of VeGF and reduced tumor growth by influencing the PGe-2-induced VeGF-signaling pathway (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The group transfected with miR-186 and control constructs exhibited the minimum number of cells passing through the chamber, which could be abolished upon transfection with PTTG1 constructs. * P<0.05. perform a pivotal role in muscle differentiation (14), miR-186 has also been found to participate in many biological and pathological processes, including cell proliferation, apoptosis and invasion (7,15). Recently, the tumor suppressive role of miR-186 has been widely reported in many cancers, such as in prostate cancer (PC), where miR-186 inhibited the expression of VeGF and reduced tumor growth by influencing the PGe-2-induced VeGF-signaling pathway (16).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our previous study reported that miR-140 was downregulated in OS tissues and functioned as a tumor suppressor in OS, as overexpression of miR-140 significantly inhibited cell proliferation in vitro and tumor growth in vivo by targeting the HDAC4 signaling pathway (6). Furthermore, miR-186 has been reported to function as a tumor suppressor in a variety of malignancies and regulate the chemosensitivity of non-small cell lung cancer cells to paclitaxel by targeting the MAPT-signaling pathway (7). In idiopathic pulmonary fibrosis cells, it has been closely related with the overexpression of collagen V and epithelial-to-mesenchymal transition (EMT) (8).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, induced overexpression of miR-137 underlined a tumour suppressive role of this miRNA in chemosensitivity by the inhibition of cell growth and angiogenesis in vivo. In a xenograft mouse model, miR-186 also showed tumour growth inhibitory functions [128]. This miRNA directly targeted MAPT and the chemosensitizing function of miR-186 was partially caused by the induction of the p53-mediated apoptotic pathway.…”
Section: Taxanesmentioning
confidence: 97%
“…Chen et al [62] reported that decreased miR-27b expression was associated with docetaxel resistance of NSCLC, while up-regulation of miR-27b could inhibit NSCLC cell viability and enhance the docetaxel sensitivity of NSCLC cells through direct inhibition of EGFR expression. Ye et al [63] showed that overexpression of miR-186 sensitized NSCLC cells to paclitaxel, whereas inhibition of miR-186 conferred resistance in NSCLC cells. In validation, miR-186 was found to be down-regulated in NSCLC patients who were paclitaxel-resistant, and this decrease was associated with poor survival.…”
Section: The Prognostic Value Of Mirnas In Nsclcmentioning
confidence: 99%